Pediatric drug utilization evaluation of cefepime and piperacillin/tazobactam - Prasopchoknapaporn P. (2023)
Background: Drug utilization evaluation (DUE) is a systematic, criteria-based assessment of medicine that aims to optimize the appropriateness of antibiotic prescription. This study aimed to evaluate the performance of the DUE on prescriptions of two commonly used antibiotics in a pediatric population, cefepime and piperacillin/tazobactam, in a tertiary care hospital. Methods: This quasi-experimental study was conducted at the Department of Pediatrics, Ramathibodi Hospital, between March 2020 and August 2021. All hospitalized children aged 1 month to 20 years who received at least one dose of cefepime or piperacillin/tazobactam were enrolled. Before implementing the DUE, cefepime and piperacillin/tazobactam prescriptions were retrospectively evaluated using the DUE criteria. During the 6 month DUE implementation period, physicians voluntarily chose to use DUE to assess the prescriptions' appropriateness. Demographic data, antibiotic use, and clinical data were recorded. Results: There were 304 prescriptions of cefepime and piperacillin/tazobactam, with 108 empirical prescriptions (72 patients) in the DUE group and 158 prescriptions (138 patients) in the non-DUE group. The appropriateness of empirical prescriptions of cefepime and piperacillin/tazobactam was significantly higher in the DUE group (93.5% vs. 83.5%; P = 0.003). Drug utilization evaluation was significantly associated with appropriate empirical prescriptions (adjusted OR 5.32: 95% CI 1.80–15.73; P = 0.003). Prescriptions in critical care wards and urinary tract infections (UTIs) were associated with not fulfilling the DUE criteria for appropriateness. Conclusions: Drug utilization evaluation could improve the appropriateness of empirical use of cefepime and piperacillin/tazobactam in pediatric patients. Patients in critical care units and with UTIs appeared to be associated with inappropriate empirical treatment.